BUILDING A TRAFFIC ROUTE TAKING INTO ACCOUNT OBSTACLES BASED ON THE A-STAR ALGORITHM USING THE PYTHON LANGUAGE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This paper explores the use of the A-Star algorithm to construct an optimal route for a mobile robot, taking into account obstacles using Python. The developed program allows you to generate a map with an arbitrary location of obstacles and automatically find the optimal path from the start to the end point, taking into account the complexity of the route. The paper presents the results of implementing the algorithm under various scenarios for the location of obstacles, which allows us to evaluate the effectiveness and reliability of the algorithm in various conditions. Experiments have shown that the A-Star algorithm provides fast and accurate route generation even in complex environments with many obstacles. The results of the study can be used to improve the autonomous navigation of mobile robots in real working conditions.